Theory of Resource-Based View (RBV): Integrated Framework of Distinctive Capability in University Performance - Wartini, Sri; Prananta, Widya; Febriatmoko, Bogy; Putri, Phany Ineke (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2024)
This research aims to examine the role of corporate strategy as a mediating influence between unique capabilities and environmental turbulence on the performance of Legal Entity Universities (Perguruan Tinggi Negeri Berbadan Hukum - PTNBH university). Corporate strategy is important in supporting unique capabilities and environmental volatility to achieve performance. The population of this study were leaders at the PTNBH University in Central Java. The sample collection technique uses purposive sampling, namely data collection, by considering the criteria: it is a state university with a legal entity, and it has been active in structural positions for at least 1 year. The number of samples was a total of 109 respondents. The results found that unique capabilities do not directly influence university performance but directly influence corporate strategy, and environmental turbulence directly influences corporate performance and strategy. The unique capabilities possessed by universities are good capital in the increasingly fierce competition because they can be used to develop higher education strategies. The results of indirect testing (mediation) show that corporate strategy plays a mediating role between unique capabilities and environmental turbulence on the performance of PTNBH University. Future researchers can combine or add other predictor variables to generalize this research.